After cochlear implantation in older adults, enhanced working memory does not fully mediate the relationship between CI and improved semantic fluency - Huber, Maria; Illg, Angelika; Reuter, Lisa; Weitgasser, Lennart (Frontiers in Aging Neuroscience, 2026)
AimStudies indicate that semantic fluency improved after cochlear implantation (CI) in older adults, but not in young and middle-aged adults. We were interested in identifying cognitive variables that are associated with this improvement. We tested whether improvements in cognition after cochlear implantation are associated with improvements in semantic fluency in older adults.MethodsWe used data from a multicenter cohort study. All dementia-free CI patients had symmetrical hearing loss that started in adulthood. The younger group (n = 20) was aged 25 and 59 years, and the older group (n = 21) was aged between 60 and 75 years. All participants underwent word fluency tests, as well as tests of working memory, cognitive flexibility, inhibition, and verbal episodic memory, immediately before and 12 months after the CI.ResultsSemantic fluency and working memory improved significantly in the older group. No significant improvement was found in the younger group. The improvement in semantic fluency in the older group correlated significantly with the improvement in working memory. Mediation analyses suggest a partial overlap between improvements in semantic fluency and working memory. The improvement in working memory accounted for 28% of the enhancement in semantic fluency.ConclusionIn older adults with hearing loss, enhanced working memory after CI did not fully mediate the relationship between CI and semantic fluency. Additional variables that also improved after CI may influence semantic fluency.